Non-Financial Feasibility Analysis on The Utilization of Cattle Livestock Waste as a Biogas - Halima, Andi Sitti; Darma, Darma; Akhnaniyanti, Akhnaniyanti (Journal of Community Based Environmental Engineering and Management, 2024)
This research aims to analyze the non-financial feasibility of using livestock waste as raw material for biogas. Qualitative data was obtained to provide an overview of the cattle farming business, the implementation of waste processing with a biogas installation, where the final result is biogas which can be utilized by livestock breeder groups and the community around the installation. The feasibility of this activity is determined using the differential semantic scale formula. The results of the non-financial feasibility analysis show that the business of using livestock waste as raw material for biogas is feasible to develop in terms of market aspects, technical aspects, management aspects, as well as social and environmental aspects. The two biogas installations granted by the regional government were able to help the community save energy.